Theories of the multinational enterprise diversity, complexity, and relevance - Hitt, Michael A.; Cheng, Joseph L. C. 1952- (Advances in international management ;, 2004)
The early research on multinational enterprises usually relied on traditional economic theory or relatively simple but powerful theories developed in the field of international business. They were developed to help us understand why firms entered international markets. However, as the field of international management has developed further, with more scholars from adjacent disciplines conducting research on issues of importance to international markets and multinational firms, newer, more diverse and complex theoretical perspectives have been developed. The present volume involves a series of invited papers focused partly on Professor Doz's recent work and on other newer and important theoretical perspectives on the multinational enterprise. These works are authored by a number of top scholars in the field from North America and Europe. The intent of this volume is to highlight and emphasize the new and diverse theoretical foci in this field (e.g., management of large groups in emerging markets, international entrepreneurship and the liabilities of foreignness) and serve as a catalyst to the increasingly important research, designed to help us understand and build a theory of the multinational firm. The book is divided into three parts, with the first focused on the new and visible theory of the metanational firm by Yves Doz and comments on this work and Yves Doz's broader contributions to the field by three top scholars in the international management field. The second part contains two works that examine the evolving nature of theory on the multinational firm in international management research. The third part contains five papers that present diverse yet highly important theoretical perspectives on the multinational enterprise. This work provides a base upon which future excellent research in the field of international management will be advanced.